TINJAUAN HUKUM TINDAK PIDANA DUGAAN MAFIA TANAH OLEH APARATUR KECAMATAN SERPONG - Ahsan Pasinringi; FX Suyud Margono; Appe Hutauruk (Collegium Studiosum Journal, 2026)
Land mafia practices in Indonesia have become a systemic phenomenon that threatens legal certainty and human rights. The contradiction between the principle of the rule of law and the vulnerability of old land title documents (Girik/Letter C) often triggers maladministration and abuse of authority by officials at the village and sub-district levels. Ideally, land governance should guarantee the protection of community rights by adhering to the General Principles of Good Governance (AAUPB), particularly the principles of accuracy and legality. This normative juridical legal research analyzes the legal implications of government maladministration in issuing invalid land transfer letters and evaluates the role of the State Administrative Court (PTUN) as an instrument for rights restoration. Through a statutory approach and case studies, it was found that the actions of officials who failed to verify documents legally fulfilled the elements of an unlawful act by the government (onrechtmatige overheidsdaad). The results of the study indicate that the PTUN plays a crucial role as a corrective and repressive instrument for victims. As reflected in Decision Number 533K/TUN/KI/2019, the judiciary is capable of restoring the rights of legitimate owners in full (restitutio in integrum). As a solution, strengthening administrative order and accelerating the digitization of land documents at the village level is necessary. This step is urgently needed to close the vulnerabilities exploited by land mafia networks to ensure legal certainty for the community.